2015
DOI: 10.3109/14767058.2015.1057811
|View full text |Cite
|
Sign up to set email alerts
|

Th1, Th2, Th17 and Treg levels in umbilical cord blood in preeclampsia

Abstract: Our data suggest that the cytokine balance is broken, encouraging the development of an exacerbated inflammatory response. Our results show that there is a shift, in the Th1/Th2, and the Th17/Treg balance, favoring skewness towards a proinflammatory status in the umbilical cord blood in preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 22 publications
5
51
1
2
Order By: Relevance
“…These findings go in hand with multiple previous studies evaluated the relation between development of PE and altered immune milieu; where Vargas-Rojas et al (22) suggested that disturbed cytokine balance during PE encourage development of an exacerbated inflammatory response with a shift towards a pro-inflammatory status. Also, Cornelius et al (23) experimentally found on transfer of Th17 cells resulting from reduced uterine perfusion in induced tissue oxidative stress, increased serum IL-6 and causes increased blood pressure and intrauterine growth restriction and concluded that autoimmune status associated with Th17 cells may have a role in pathogenesis of PE.…”
contrasting
confidence: 54%
“…These findings go in hand with multiple previous studies evaluated the relation between development of PE and altered immune milieu; where Vargas-Rojas et al (22) suggested that disturbed cytokine balance during PE encourage development of an exacerbated inflammatory response with a shift towards a pro-inflammatory status. Also, Cornelius et al (23) experimentally found on transfer of Th17 cells resulting from reduced uterine perfusion in induced tissue oxidative stress, increased serum IL-6 and causes increased blood pressure and intrauterine growth restriction and concluded that autoimmune status associated with Th17 cells may have a role in pathogenesis of PE.…”
contrasting
confidence: 54%
“…However, it also has an important role in induction of the protective immune response against extracellular bacteria or fungal pathogens at mucosal surfaces (608, 611623). Th17 cells seem to participate in successful pregnancy processes and can be lower in PE (624626), although more studies show them as higher (599, 627635) or unchanged (636, 637). One interpretation, consistent with the present thesis, is that the antimicrobial effects of placental IL-17 relative to T reg cells are compromised during PE (599, 633, 638).…”
Section: Effects Of Lps and Other Microbial Antigens On Disrupting Trmentioning
confidence: 99%
“…Production of Th1 cytokines is inhibited during normal pregnancy, and their excessive expression is likely to induce preeclampsia (Vargas-Rojas et al, 2016). Th1 cells secrete interleukin-2 (IL-2), interferon-g (IFN-g), and tumor necrosis factor-a, whereas Th2 cells produce IL-6, IL-10, IL-4, and TGF-b (Kiyomi et al, 2015;Talaat et al, 2015;Yuan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%